Lived Experiences of Antenatal Services Utilization among Pregnant Women during COVID- 19 Pandemic - Rafiat Anokwuru; Fhumulani Mulaudzi (Mashhad University of Medical Sciences, 2022)
Background & aim: The process of country lockdown, social distancing and limited access to services as a result of COVID-19 pandemic brought a change to established patterns in the antenatal care services in the primary health care systems. The current article presents the lived experience of utilization of antenatal services among pregnant women during covid-19 pandemic.Methods: A descriptive phenomenological design was used to elicit data from 12 pregnant women. Pregnant women who booked in healthcare services were recruited from Gauteng and Limpopo province in South Africa using a purposive and snowballing sampling method.  The data were collected and recorded from July to August 2020, either through the telephone or e-platforms (Zoom and google meet).  The recorded data was transcribed and analyzed using the steps outlined by Sundler et all.Results: Four themes emerged from the analysed data. Three themes focused on the experiences of the pregnant women showing the negative impact of the COVID-19 pandemic on antenatal services including: fear of contracting COVID-19 during antenatal; limited available antenatal services and coping with the new normal. The fourth theme is need for digital health education which focused on the antenatal services development.Conclusion: The study showed that the covid-19 pandemic negatively impacted utilization  of antenatal services among pregnant women. It is therefore important for the health departments to adopt innovative ways to improve utilization  of antenatal services among pregnant women during a pandemic situation such as the COVID-19 pandemic.